2014
DOI: 10.1111/bld.12092
|View full text |Cite
|
Sign up to set email alerts
|

When satisfaction is not directly related to the support services received: understanding parents' varied experiences with specialised services for children with developmental disabilities

Abstract: Accessible summary Parents of children with developmental disabilities need formal support services to help them. Their well‐being and satisfaction depend on how the support services respond to their needs. Some parents want to be more involved in decisions about support services and intervention for the best of their child's interests. Other parents believe that the child's best interest are addressed adequately by the professionals who deliver the services. Summary Parents of children with developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…Robert et al. () found that access to information helped parents of children with disabilities adjust emotionally, access services and improve management of their child's behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robert et al. () found that access to information helped parents of children with disabilities adjust emotionally, access services and improve management of their child's behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of an information booklet could act as a reference point, thus reducing parental uncertainty and distress. Robert et al (2015) found that access to information helped parents of children with disabilities adjust emotionally, access services and improve management of their child's behaviour.…”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation
“…Formal services. The literature indicated that the use of formal services for the child with the disability can have negative impacts on families (Dowling & Dolan, 2001;Neely-Barnes & Marcenko, 2004;Robert, Leblanc, & Boyer, 2015;Rogers & Hogan, 2003). Dowling and Dolan (2001) reported that sources of anxiety included long wait lists, having to reapply regularly for services, the cost and time of travel to and from services, long wait-times at appointments, missed recreational activities for the whole family, and the lack of flexibility and responsiveness of service providers.…”
Section: Support Factorsmentioning
confidence: 99%
“…Client satisfaction can be based on numerous factors, such as healthcare settings, technical management, and features of interpersonal care and staff interactions [ 2 ]. Among these factors, most authors believe that the patient–staff interaction has the best effect on client satisfaction [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%